2019
DOI: 10.1111/ene.13981
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and echocardiographic characteristics of cardioembolic stroke

Abstract: Background and purpose Ischaemic stroke frequently has a cardioembolic (CE) source. Clinical and echocardiographic parameters associated with CE stroke were evaluated. Methods In all, 93 consecutive ischaemic stroke patients who underwent a transthoracic echocardiogram were retrospectively analysed; strokes were classified by TOAST (Trial of Org 10172 in Acute Stroke Treatment) criteria. Echocardiographic parameters related to CE stroke, including left atrial volumes and function, were compared to 73 healthy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
1
10
0
2
Order By: Relevance
“…Left atrial dilation and the presence of LV thrombus are recognized risk factors for ischemic stroke that were observed to occur with greater frequency in patients who had ischemic stroke in our population. [23][24][25] The burden of ischemic stroke in patients less than 55 years of age in our population is congruent with the observation that incidence of ischemic stroke, particularly large vessel occlusive stroke, has occurred with higher incidence in younger patients with COVID-19 compared to controls. 26 An elevated admission systolic blood pressure, defined in this study as >140 mmHg, was significantly higher in patients with ischemic stroke despite diagnosis of ischemic stroke occurring a median 7 days (1-17) from admission and was also included.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Left atrial dilation and the presence of LV thrombus are recognized risk factors for ischemic stroke that were observed to occur with greater frequency in patients who had ischemic stroke in our population. [23][24][25] The burden of ischemic stroke in patients less than 55 years of age in our population is congruent with the observation that incidence of ischemic stroke, particularly large vessel occlusive stroke, has occurred with higher incidence in younger patients with COVID-19 compared to controls. 26 An elevated admission systolic blood pressure, defined in this study as >140 mmHg, was significantly higher in patients with ischemic stroke despite diagnosis of ischemic stroke occurring a median 7 days (1-17) from admission and was also included.…”
Section: Discussionsupporting
confidence: 80%
“… 2 , 3 , 4 In retrospective studies, ischemic stroke has been identified in 0.5-5.8% of patients hospitalized with COVID-19. 5 , 6 , 7 , 8 , 9 , 10 Infection with COVID-19 has been independently associated with acute ischemic stroke compared with control subjects and the severity of COVID-19 syndrome correlates with risk acute stroke. 9 , 11 The likelihood of ischemic stroke is markedly higher in patients hospitalized with COVID-19 infection compared with controls hospitalized with influenza infection.…”
Section: Introductionmentioning
confidence: 96%
“…Specialised tests such as vasculitis and thrombophilia screens were performed in a small group of patients where it was determined by the treating physician to be clinically indicated. We have previously examined echocardiographic data that were available in a subgroup of 93 stroke patients . CHADS 2 and CHA 2 DS 2 ‐VASC scores on presentation were calculated in the subgroup with AF.…”
Section: Methodsmentioning
confidence: 99%
“…Полученные различия функциональных маркеров ЛП при сравнении группы КЭИ с другими подтипами инсульта соответствуют результатам исследования A. Ferkh и соавт. (2019) [28] Выполненное нами исследование также выявило различия в сывороточной концентрации NT-proBNP между пациентами с КЭИ и КИ/неКЭИ. Пороговая величина пептида, позволяющая дифференцировать КЭИ и неКЭИ, составила 316 пг/мл, что несколько ниже значения, полученного J. Zhao и соавт.…”
Section: General Characteristics Of the Examined Groupsunclassified
“…Таким образом, нормальные значения LAEF отражают функциональную состоятельность миокарда предсердий, при которой возможна адаптивная компенсация за счет уменьшения доли пассивной составляющей, а процессы ремоделирования, связанные с ФП, несмотря на дилатацию ЛП, обратимы [31]. В то же время другие авторы [28,32] рассматривают LAEF в качестве показателя, отражающего именно резервуарную функцию ЛП. На наш взгляд, LAEF характеризует единый процесс, ассоциированный не только с механизмом передачи крови из ЛП в ЛЖ, но и с изначальным объемом депонированной крови.…”
Section: чувствительность и специфичность эхокардиографических маркеров предсердной кардиопатии и Nt-probnp в дифференциации кэи и некэиunclassified